Taxine alkaloid poisoning successfully supported with venoarterial extracorporeal membrane oxygenation: a case report. Issue 2 (11th February 2022) - Ward, Catherine; Meeks, Daveena; Trimlett, Richard; Alçada, Joana
Abstract: Background: Ingestion of the berries of the European yew tree can result in fatal cardiac arrhythmias. Case summary: A 53-year-old female presented to our emergency department following ingestion of ∼200 European yew tree berries. At presentation, she was in cardiogenic shock due to a mixture of tachy- and bradyarrhythmias including ventricular tachycardia, atrial fibrillation with slow ventricular response and prolonged ventricular conduction, and periods of asystole. She was referred to a specialist cardiac centre and promptly established on mechanical circulatory support with venoarterial extracorporeal membrane oxygenation (V-A ECMO) by a retrieval team. Following resolution of her arrhythmias, she was weaned from V-A ECMO after 4 days of support and was discharged home with full neurological recovery on Day 12. Discussion: Poisoning can lead to acute reversible but potentially fatal cardiogenic shock. We believe that access to prompt initiation of V-A ECMO was key to this patient's survival.